2018
DOI: 10.1063/1.5021348
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous solvation of Mg(ii) and Ca(ii): A Born-Oppenheimer molecular dynamics study of microhydrated gas phase clusters

Abstract: The hydration features of [Mg(HO)] and [Ca(HO)] clusters with n = 3-6, 8, 18, and 27 were studied by means of Born-Oppenheimer molecular dynamics simulations at the B3LYP/6-31+G** level of theory. For both ions, it is energetically more favorable to have all water molecules in the first hydration shell when n ≤ 6, but stable lower coordination average structures with one water molecule not directly interacting with the ion were found for Mg at room temperature, showing signatures of proton transfer events for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 72 publications
2
25
0
Order By: Relevance
“…From the k a cum values of the implicitly solvated clusters, as shown in Table 4, we observed the implicit addition of outer shells to [Mg(H 2 O)n] 2+ (n = 1-6) clusters to increase in stability alongside increasing CN, the results revealing a CN of 6 to result in the most stable configuration due to the Mg-O and HB interactions. The CN of 6, as suggested from local mode analysis, agrees with recent experimental [16,19,21,22,24] and computational works [20,32,34,39,[41][42][43][44]46,47,49,51]. In this work, via the utilization of cumulative local mode stretching force constants k a cum , we observed the divalent Mg ion to coordinate with up to six water molecules, whereas in our previous work regarding hydrated calcium clusters, the divalent Ca ion was observed to undergo coordination with up to eight water molecules [106].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…From the k a cum values of the implicitly solvated clusters, as shown in Table 4, we observed the implicit addition of outer shells to [Mg(H 2 O)n] 2+ (n = 1-6) clusters to increase in stability alongside increasing CN, the results revealing a CN of 6 to result in the most stable configuration due to the Mg-O and HB interactions. The CN of 6, as suggested from local mode analysis, agrees with recent experimental [16,19,21,22,24] and computational works [20,32,34,39,[41][42][43][44]46,47,49,51]. In this work, via the utilization of cumulative local mode stretching force constants k a cum , we observed the divalent Mg ion to coordinate with up to six water molecules, whereas in our previous work regarding hydrated calcium clusters, the divalent Ca ion was observed to undergo coordination with up to eight water molecules [106].…”
Section: Resultssupporting
confidence: 89%
“…The more restricted CN of the Mg 2+ has previously been attributed to the smaller ion size [39,107,108], whereas the larger size of the Ca 2+ ion has been linked to weaker inner ion-solvent interactions in retrospect to that of the hydrated Mg 2+ ion [51]. As shown by Tables 3 and 5, the k a cum values of explicitly hydrated systems, based upon inner ionsolvent interactions, are larger for [Mg(H 2 O) n ] 2+ (n = 1-6) (1-6) clusters in comparison to that of their Ca 2+ counterparts by differences of 0.601 to 1.341 mdyn/Å (i.e., 1a-6a in 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a semiempirical coupling method with a basinhopping global optimization approach, Wales and co-workers searched the low-lying structures of Ca 2+ (H 2 O) n with n 1-20 clusters, showing that Ca 2+ prefers to locate at the center of the cluster surrounded by eight adjacent water molecules (González et al, 2005). The CN of the calcium ion attained by Monte Carlo (MC) (Bernal-Uruchurtu and Ortega-Blake, 1995) and MD (Obst and Bradaczek, 1996;Tongraar et al, 1997;Todorova et al, 2008;Wanprakhon et al, 2011;León-Pimentel et al, 2018) studies varies from 6 to 10. However, the results from DFT calculations showed that there are six water molecules in the first hydration shell (Megyes et al, 2004;Peschke et al, 2000;Carl et al, 2007;Lei and Pan, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…While this permits accurate local exploration and proper account of anharmonic and temperature effects on populations and vibrational spectra, it is not yet amenable to extensive exploration of structural space. 15,[20][21][22] Global methods such as basin-hopping global optimization, [23][24][25] simulated annealing 26 and various genetic algorithms 27,28 have been developed to improve the energylandscape exploration. Approximate quantum methods have been used to extend the range of system sizes in comparison with the DFT framework.…”
Section: Introductionmentioning
confidence: 99%